Self-Deception in Psychology and Ethics with an Emphasis on the Views of Ayatollah Javadi Amoli - mahdi alizadeh; ali akbar teymory (اخلاق وحیانی, 2017)
Self-deception is a common phenomenon, which every human being experiences it in his/her life. However, it is not easy to explain its nature and the effective factors in its formation. In self-deception, the individual does something that brings him/her wrong belief and false knowledge. This brief definition was not acceptable for many scholars and made them redefine self-deception by appealing to the very concept of deception. The assimilation of these two phenomenon leads to contradiction and, then, to finding a way out of this problem. Although the term self-deception has not appeared in Islamic heritage, the background of its occurrence has been well discussed under another, which is arrogance. According to Islamic views, there are ten factors for self-deception, which being aware of them, individuals can keep themselves away from self-deception. This paper, which has a descriptive-analytic methodology, in the first place looks at the definition and nature of self-deception, and then turns to the epistemic-psychological factors in its formation according to the Islamic views, especially the views of Ayatollah Javadi Amoli. At the end there is a discussion on the ethical implications of this phenomenon.